Towards A Digitalized Collaborative Zakat Management System for Accelerating Good Governance Practices in the New Normal - Roshayani Arshad; Ruhaini Muda; Ramesh Nair (USIM Press, 2024)
JMIFR Vol.18 No. 2 (Dec) 2021